Sistema de transmisión multiportadora mediante multiplexación por división de frecuencia generalizado (GFDM) - Flores Tipán, Lizeth Carolina (2017)
Telecommunications have contributed to the development of society, its improvement, is closely related with the changes and technological advances, that is the reason why the communication systems have been adapting according with the needs and increasingly demanding requirements of the users. In order to optimize the use of the frequency spectrum, new multicarrier systems have been proposed as the key to the 5G infrastructure, GFDM (Generalized Frequency Division Multiplexing) is including among them. It works with an envelope processing method to the filtering, making the data frame smaller and achieving a delay in milliseconds. For a better understanding the operation of Generalized Frequency Division Multiplexing, this project implements an off - line multicarrier transmission system, using Matlab 2013 as simulation tool, and signal analyzer equipment in both time and frequency domain. On the development of this work a transmission of random data is performed, which are firstly subjected to 16-QAM modulation, then passed to the GFDM process through the application of the RRC (Root Raised Cosine) rectangular filter, and finally obtain the transmission signal. Then the signal is generated trough AWG generator, and observed by the Real Time Oscilloscope, after that received data is processed in Matlab again. At the end, an analysis of the data sent and received is performed, using parameters such as BER (Bit Error Rate) and EVM (Error Vector Magnitude), the first allows to know how much error exists between the transmitted and received bits, second one evaluates the QAM symbols in both transmission and reception.